2012
DOI: 10.1097/hcr.0b013e31825d29ee
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cholesterol Hyperabsorbers and Hyperproducers Based on Comparative Low-Density Lipoprotein Reductions Achieved by Ezetimibe Versus Statins

Abstract: This study demonstrated that the LDL response to ezetimibe is inversely related to the response to statin. This lends support to the hypothesis that some patients may be hyperabsorbers of cholesterol while others may be hyperproducers. This suggests that a less than expected response to the initial dose of statin in a patient would likely require the addition of ezetimibe to achieve the recommended target levels in spite of the use of maximum dose statin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Moreover, studies which monitored plasma cholesterol levels have shown that individuals vary significantly in their responses to dietary cholesterol [44], [45], possibly due to intrinsic differences in cholesterol absorption [46] and have resulted in normolipidemic individuals being classified as either hypo or hyper responsders [47], [48]. Similarly, it has recently been suggested that certain individuals are hyperproducers of cholesterol while others are hyperabsorbers [49]. These findings endorse the view that regulation of whole-body lipid metabolism is underpinned by a variety of extrinsic and intrinsic factors acting simultaneously.…”
Section: Lipid Metabolism and Healthy Agingmentioning
confidence: 99%
“…Moreover, studies which monitored plasma cholesterol levels have shown that individuals vary significantly in their responses to dietary cholesterol [44], [45], possibly due to intrinsic differences in cholesterol absorption [46] and have resulted in normolipidemic individuals being classified as either hypo or hyper responsders [47], [48]. Similarly, it has recently been suggested that certain individuals are hyperproducers of cholesterol while others are hyperabsorbers [49]. These findings endorse the view that regulation of whole-body lipid metabolism is underpinned by a variety of extrinsic and intrinsic factors acting simultaneously.…”
Section: Lipid Metabolism and Healthy Agingmentioning
confidence: 99%
“…People also differ in terms of the intensity of cholesterol synthesis (Lecerf and Lorgeril, 2011). Some people may be hyperabsorbers of cholesterol while others may be hyperproducers (Senaratne et al, 2012).…”
Section: Dietary Cholesterolmentioning
confidence: 99%